Anthropometric parameters of obesity can be alternative biomarkers for the potential cardiac dysfunction in obese children - Sun, Jing; Wang, Li; Lin, Yingjiong; Liu, Yunfeng; Liu, Fei; Liu, Xumei; Dong, Wenyan; Cai, Wenqian; Chen, Huimin; Xiao, Minhua; Luo, Hongfeng; Liu, Xihong; et al. (Frontiers in Cardiovascular Medicine, 2022)
Childhood obesity, as one of the potential risk factors of cardiovascular diseases, is closely associated with the incidence of cardiovascular disease at a younger age and has become a public health concern worldwide. However, its potential effects on the cardiovascular system have still remained elusive. In this study, we systematically evaluated the cardiovascular characteristics of 79 obese children and 161 normal weight children in Guangzhou (China) using the potential biomarkers for cardiovascular disease. Compared with normal weight children, obese children not only exhibited significantly higher levels of creatine kinase (CK), lactate dehydrogenase (LHD), soluble fms-like tyrosine kinase-1 (s-Flt-1), high-sensitivity C-reactive protein (hs-CRP), and uric acid (UA) (p = 0.0062, 0.0012, 0.0013, 0.0225, and <0.0001, respectively) but also significantly higher diastolic blood pressure (p = 0.0074) and the heart rate (p = 0.0049) were found in obese children. Of 79 obese children, cardiac functions of 40 cases were further assessed by color Doppler echocardiography. The results showed that there were significant differences between the obesity group and the healthy weight group in terms of interventricular septal wall thickness at end-diastolic (IVSd), the left ventricular posterior wall thickness at end-diastolic (LVPWD), and aortic annulus (AO) (p < 0.0001, 0.0003, and p < 0.0001, respectively). Besides, the left and/or right ventricular functions were declined in 52.4% of obese children. Correlation analysis revealed that the anthropometric parameters of obesity were not only significantly correlated with a blood lipid profile but also exhibited a more significant correlation with most of the parameters of cardiac dysfunction than a blood lipid profile. Therefore, our study indicated that obese children in Guangzhou suffered from functional damages related to cardiovascular events, which were characterized by cardiac dysfunction, and the anthropometric parameters of obesity could be economically alternative biomarkers for monitoring of cardiac dysfunction in obese children.